A comparative evaluation of efficacy of gingival retraction using polyvinyl siloxane foam retraction system, vinyl polysiloxane paste retraction system, and copper wire reinforced retraction cord in endodontically treated teeth: An in vivo study - Sonal Mehta; Hemali Virani; Sarfaraz Memon; Narendra Nirmal (Contemporary Clinical Dentistry, 2019)
Purpose of the Study: The purpose of the study is to evaluate the efficacy of three gingival retraction systems such as polyvinyl siloxane foam retraction system (magic foam cord; Coltene/WhaledentInc), polysiloxane paste retraction system (GingiTrac; Centrix), and aluminum chloride impregnated twisted retraction cord (Stay-Put; Roeko) in endodontically treated teeth. Materials and Methods: Patients who were endodontically treated for molars and requiring crown for the same, were selected for the present study with sample size of 45. The 45 participants were divided into three groups. Group 1 was treated with Stay-Put, Group 2 with Magic Foam, and Group 3 with GingiTrac. About 90 elastomeric impressions of the participants were taken—45 impressions before retraction and 45 impressions after retraction. The sulcus width was measured on the die obtained from the elastomeric impressions by placing the dies under OVI-200 optical microscope in combination with X soft imaging system software attached to a computer. Results: The study indicated 0.465627 mm ± 0.063066 mm of gingival retraction for aluminum chloride impregnated retraction cord, 0.210993 mm ± 0.067358 mm of gingival retraction for GingiTrac paste, and 0.294147 mm ± 0.056697 mm of gingival retraction for magic foam cord. Conclusion: The study data indicated that the new retraction systems are not as effective as the standard retraction cord; however, of the two new systems the Magic Foam system did prove to be effective enough for clinical use. The GingiTrac system failed to achieve the minimum gingival retraction required and hence may not be suitable for clinical use.